Effect of carboxymethyl cellulose and baking conditions on in-vitro starch digestibility and physico-textural characteristics of low glycemic index gluten-free rice cookies. (April 2021) - Naseer, Bazila; Naik, Haroon Rashid; Hussain, Syed Zameer; Zargar, Imtiyaz; Beenish; Bhat, Tashooq Ahmad; Nazir, Nageena
Abstract: In this study, we aimed to formulate low glycemic index gluten-free cookies from high amylose rice flour by modifying baking conditions and ingredient composition. Baking temperature, baking time, and concentration of carboxymethyl cellulose were varied between 170 and 190 °C, 12–25 min, and 0.2–1%, respectively, using central composite rotatable design. Among the physical quality attributes, spread ratio and hardness of cookies increased predominantly with the increase in baking temperature. Resistant starch content and overall acceptability of cookies increased prominently, whereas predicted glycemic index and glycemic load decreased with the increase in the concentration of carboxymethyl cellulose. Design expert predicted baking temperature of 185 °C, baking time of 22 min, and 0.8% concentration of carboxymethyl cellulose as desirable conditions for the development of gluten-free low-glycemic index cookies from rice flour. Dietary fiber content of developed cookies was recorded as 4.66%. In-vitro starch digestibility results confirmed that resistant starch increased from 2.85% in rice flour to 7.20% in cookies, whereas predicted glycemic index and glycemic load decreased from 50.12 to 30.07 in rice flour to 44.60 to 17.51 in cookies, respectively. Overall acceptability of cookies was recorded as 8.90 on a 9-point hedonic scale. Highlights: Interventions were made in baking process to develop Low GI gluten free rice cookies. CMC level was also optimized to improvise the physico-textural attributes of cookies. Resistant starch, pGI and GL were recorded as 7.20%, 44.60 and 17.51 in final cookies. A new perspective to develop rice cookies for diabetic and celiac disease patients was presented.